Produção de sentidos da língua portuguesa por surdos usuários da língua brasileira de sinais - Machado, Leonardo Lúcio Vieira (2015)
Our experience by living with deaf people and their issues with the Portuguese language makes us face with lines like: I do not know words. I want to learn words. So we asked ourselves: What does "learning words" mean? So, the purpose of this work is a reflection on the production of meaning in the undertaken reading from Portuguese texts by these individuals. The fact that these individuals are Brazilian Sign Language (Libras) users, a visual-space language mode, creates difficulty for teachers in dealing with the modalities of these languages and teaching Portuguese as L2 for the deaf individual. In order to offer more strategies in classrooms to create more opportunities to teaching the use of these languages for deaf individuals, there is the challenge to answer the central question of this research: how does the production of meaning in signs reading of a oral-hearing modality of language, as is the Portuguese language, occurs? For this task we have as main objective to understand the process of creating meaning in reading by deaf individuals (members of a visual-spatial language), of certain linguistic signs found in the texts in Portuguese (oral and auditory modality). The theoretical framework is based on Saussure's concepts developed by Fiorin (2006, 2008, 2010, 2013) and Benveniste (2005, 2006) about language, idiom, speak, sign, statement, direction, text and speech. And the prospect of the research lies in Applied Linguistics and its connection with the Social Sciences in the reflection about the problem of the language and its uses. So the used methodology will be the Integral and Systemic Action Research described by Morin (1996) and Barbier (2000), as has the participation and absolute intervention by the researcher and researched. For data analysis, the proposal is a description of the classes with a discussion based on the theoretical framework of categories sign, text and speech. So the idea is to end with the suggestions of some strategies of teaching Portuguese as L2 based on the perspective of Applied Linguistics from the results presented in the production of meanings.